Utilizing Multimedia Learning Platforms to Address Participation Challenges in Online Religious Education: The Digital SKI Case Study - Lisnawati; Arifah Choirun Nisa; Uswatun Hasanah; Alief Budiyono (Journal of Innovation and Research in Primary Education, 2026)
The transition to online learning in Islamic educational institutions has precipitated significant student participation challenges, particularly in Islamic Cultural History (SKI) instruction where traditional pedagogical approaches demonstrate limited effectiveness in sustaining engagement. This study analyzed the effectiveness of Digital SKI, a comprehensive multimedia learning platform, in enhancing student participation during online SKI instruction at MTs Negeri 4 Rembang. Employing a descriptive qualitative approach, this research investigated 102 seventh-grade students across three classes. Data were collected through participatory observation, attendance records, platform analytics, and structured questionnaires administered via Google Forms. Analysis involved descriptive statistics for quantitative data and thematic analysis for qualitative responses. Digital SKI implementation yielded substantial participation improvements, with attendance rates increasing from 45-62% to 62-85% across classes, representing gains of 9-30 percentage points. Student reflections revealed overwhelmingly positive perceptions, with 96% of respondents expressing favorable attitudes. Students particularly valued gamification features, multimedia content including e-books, animated videos, and historical films, and flexible accessibility through Linktree integration. Digital SKI effectively enhanced student participation by activating behavioral, cognitive, and affective engagement dimensions through integrated multimedia resources, gamification, and interactive assessments. These findings demonstrate that comprehensive digital learning ecosystems can successfully address participation crises in online religious education contexts.